1996
DOI: 10.2527/1996.7481888x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary copper and fat on nutrient utilization, digestive enzyme activities, and tissue mineral levels in weanling pigs.

Abstract: Two 15-d nutrient balance trials were conducted using a total of 32 weanling barrows (averaging 6.8 kg, 26 d). The effect of the addition of 15 or 250 ppm Cu (as CuSO4.5H2O) to diets containing 0 or 5% added animal fat on nutrient utilization, digestive enzyme activities, and tissue mineral levels in weanling pigs was investigated. In each trial, four groups of four littermate barrows were randomly assigned to one of four treatments in a 2 x 2 factorial arrangement. The addition of 250 ppm Cu improved apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
35
3
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 29 publications
14
35
3
2
Order By: Relevance
“…The discrepancy may be attributed to Zn source and animals used in the experiments. The lack of effect of CuSO 4 on the enzyme activities in this experiment is in agreement with previous reports (Luo and Dove, 1996;Hedemann et al, 2006). Surprisingly, the addition of CuSO 4 to the diet containing 1500 mg Zn/kg TBZC had a negative effect on trypsin activities in duodenal contents and chymotrypsin activities in both pancreatic tissue homogenates and jejunum contents.…”
Section: Resultssupporting
confidence: 82%
“…The discrepancy may be attributed to Zn source and animals used in the experiments. The lack of effect of CuSO 4 on the enzyme activities in this experiment is in agreement with previous reports (Luo and Dove, 1996;Hedemann et al, 2006). Surprisingly, the addition of CuSO 4 to the diet containing 1500 mg Zn/kg TBZC had a negative effect on trypsin activities in duodenal contents and chymotrypsin activities in both pancreatic tissue homogenates and jejunum contents.…”
Section: Resultssupporting
confidence: 82%
“…A high intake of copper was reported to decrease iron in pig liver (17,18) and plasma (18). Our findings are just the reverse.…”
Section: Effect Of Copper Bhasm On Tissue Distribution Of Essential Econtrasting
confidence: 56%
“…Shurson et al (1990) also found that high Cu generally reduces villus height and width and crypt depth in germ-free pigs, whereas it increases these parameters in conventional pigs. 250 ppm Cu (as copper sulphate) has also been shown to stimulate intestinal lipase and phospholipase A 2 activities, leading to an improvement of dietary fat digestibility in weaning pigs (Luo et al, 1996), and to increase protein utilisation, most probably through activation of pepsin activity (Kirschgessner et al, 1976). These findings are in agreement with investigations with growth promoting antibiotics which have also been found to increase fat and protein digestibility.…”
Section: St Si1 Si2 Si3 Cae Co1 Co2 Rec St Si1 Si2 Si3 Cae Co1 Co2 Recmentioning
confidence: 99%